Thermal analysis of lithium-ion batteries with square frame geometries by theoretical simulations - Miranda, D. (2017)
Thermal analysis of battery geometries is essential for applications, as the thermal behavior of a battery influences its cycling life. Two geometries, square frame and conventional, have been studied for a scan rate of 290C. The square frame shows a capacity value of 290,15 Ahm−2 which is 446 times higher than the one for the conventional geometry, when the area is maintained constant for all components. In the adiabatic model, the square frame geometry has higher capacity value in comparison to the conventional geometry.